Uterine serous carcinoma: assessing association between genomics and patterns of metastasis - Alessandrino, Francesco; Goncalves, Nicole; Metalonis, Sarah Wishnek; Luna, Cibele; Mason, Matthew M.; Lyu, Jiangnan; Huang, Marilyn (Frontiers in Oncology, 2023)
Background: Uterine serous carcinoma (USC) is an aggressive subtype of endometrial carcinoma which has been increasing at alarming rates, particularly among Asian, Hispanic and Black women. USC has not been well characterized in terms of mutational status, pattern of metastases and survival. Objective: To investigate the association between sites of recurrence and metastases of USC, mutational status, race, and overall survival (OS). Methods: This single-center retrospective study evaluated patients with biopsy-proven USC that underwent genomic testing between January 2015 and July 2021. Association between genomic profile and sites of metastases or recurrence was performed using χ2 or Fisher’s exact test. Survival curves for ethnicity and race, mutations, sites of metastasis/recurrence were estimated using the Kaplan-Meier method and compared with log-rank test. Cox proportional hazard regression models were used to examine the association between OS with age, race, ethnicity, mutational status, and sites of metastasis/recurrence. Statistical analyses were performed using SAS Software Version 9.4. Results: The study included 67 women (mean age 65.8 years, range 44-82) with 52 non-Hispanic women (78%) and 33 Black women (49%). The most common mutation was TP53 (55/58 women, 95%). The peritoneum was the most common site of metastasis (29/33, 88%) and recurrence (8/27, 30%). PR expression was more common in women with nodal metastases (p=0.02) and non-Hispanic women (p=0.01). ERBB2 alterations were more common in women with vaginal cuff recurrence (p=0.02), while PIK3CA mutation was more common in women with liver metastases (p=0.048). ARID1A mutation and presence of recurrence or metastases to the liver were associated with lower OS (Hazard Ratio (HR): 31.87; 95%CI: 3.21, 316.9; p<0.001 and HR: 5.66; 95%CI: 1.2, 26.79; p=0.01, respectively). In the bivariable Cox model, the presence of metastasis/recurrence to the liver and/or the peritoneum were both independent significant predictors of OS (HR: 9.8; 95%CI: 1.85-52.7; p=0.007 and HR: 2.7; 95%CI: 1.02-7.1; p=0.04, respectively). Conclusions: TP53 is often mutated in USC, which most commonly metastasize and recur in the peritoneum. OS was shorter in women with ARID1A mutations and with metastasis/recurrence to the liver. The presence of metastasis/recurrence to liver and/or peritoneum were independently associated with shorter OS.